Large Difference in Latency of Visual Evoked Potential P100 Peak in Case of Pattern and Flash Stimulation in a Multiple Sclerosis Patient - Shushtarian, Seyed Mohammad Masoud; Fatemian, Nazanin (Journal of Ophthalmic and Optometric Sciences, 2021)
The visual evoked potential is one of the suitable techniques for the diagnosis of multiple sclerosis. There are two stimulation techniques, i.e., pattern reversal checkerboard and flash, to record visually evoked potential. Flash type of stimulation is used in patients with poor visual acuity. Here we report the VEP recording of a multiple sclerosis patients with two types of stimulation and an extraordinarily significant P100 peak latency difference observed between the two types of stimulation.